Single‐particle XFEL 3D reconstruction of ribosome‐size particles based on Fourier slice matching: requirements to reach subnanometer resolution. (30th May 2018) - Nakano, Miki; Miyashita, Osamu; Jonic, Slavica; Tokuhisa, Atsushi; Tama, Florence
Abstract : Three‐dimensional structure reconstructions of ribosome from simulated XFEL diffraction patterns using a slice‐matching approach provide insights on how XFEL single‐particle experimental conditions and the amount of data affect the resulting resolution. Abstract : Three‐dimensional (3D) structures of biomolecules provide insight into their functions. Using X‐ray free‐electron laser (XFEL) scattering experiments, it was possible to observe biomolecules that are difficult to crystallize, under conditions that are similar to their natural environment. However, resolving 3D structure from XFEL data is not without its challenges. For example, strong beam intensity is required to obtain sufficient diffraction signal and the beam incidence angles to the molecule need to be estimated for diffraction patterns with significant noise. Therefore, it is important to quantitatively assess how the experimental conditions such as the amount of data and their quality affect the expected resolution of the resulting 3D models. In this study, as an example, the restoration of 3D structure of ribosome from two‐dimensional diffraction patterns created by simulation is shown. Tests are performed using the diffraction patterns simulated for different beam intensities and using different numbers of these patterns. Guidelines for selecting parameters for slice‐matching 3D reconstruction procedures are established. Also, the minimum requirements for XFEL experimental conditions to obtain diffraction patterns for reconstructing molecular structures to a high‐resolution of a few nanometers are discussed.